A novel human stem cell model for Coffin-Siris syndrome-like syndrome reveals the importance of SOX11 dosage for neuronal differentiation and survival - Turan, Sören; Börstler, Tom; Kavyanifar, Atria; Loskarn, Sandra; Reis, André; Winner, Beate; Lie, Dieter Chichung (Human Molecular Genetics, 2019)
The SOXC transcription factors Sox4, Sox11 and Sox12, are critical neurodevelopmental regulators that are thought to function in a highly redundant fashion. Surprisingly, heterozygous missense mutations or deletions of SOX11 were recently detected in patients with Coffin-Siris syndrome-like syndrome (CSSLS), a neurodevelopmental disorder associated with intellectual disability, demonstrating that in humans SOX11 haploinsufficiency cannot be compensated and raising the question of the function of SOX11 in human neurodevelopment. Here, we describe the generation of SOX11(+/-) heterozygous human embryonic stem cell (hESC) lines by CRISPR/Cas9 genome engineering. SOX11 haploinsufficiency impaired the generation of neurons and resulted in a proliferation/differentiation imbalance of neural precursor cells and enhanced neuronal cell death. Using the SOX11(+/-) hESC model we provide for the first time experimental evidence that SOX11 haploinsufficiency is sufficient to impair key processes of human neurodevelopment, giving a first insight into the pathophysiology of CSSLS and SOX11 function in human neurodevelopment.
CRIS-Team WoS Importer:2019-11-12

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B+/- hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B+/- hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.
CRIS-Team Scopus Importer:2020-07-24

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome - Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Wiesmann da Silva Reis, André; Lie, Dieter Chichung; Winner, Beate; Turan, Sören (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B(+/-) hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B(+/-) hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.

CRISPR/Cas9 mediated generation of human ARID1B heterozygous knockout hESC lines to model Coffin-Siris syndrome. - Turan, Soeren; Winner, Beate; Winner, Beate; Krumbiegel, Mandy; Wiesmann da Silva Reis, André; Lie, Dieter Chichung; Börstler, Tom; Wend, Holger; Krumbiegel, Mandy; Kavyanifar, Atria; Reis, Andre; Lie, Dieter Chichung (Stem Cell Research, 2020)
ARID1B haploinsufficiency induced by missense or nonsense mutations of ARID1B is a cause of Coffin-Siris syndrome (CSS), a neurodevelopmental disorder associated with intellectual disability. At present, no appropriate human stem cell model for ARID1B-associated CSS has been reported. Here, we describe the generation and validation of ARID1B+/- hESCs by introducing out of frame deletions into exon 5 or 6 of ARID1B with CRISPR/Cas9 genome editing. These ARID1B+/- hESC lines allow to study the pathophysiology of ARID1B-associated CSS in 2D and 3D models of human neurodevelopment.

Generation and Validation of Human Pluripotent Stern Cell Disease Models Using CRISPR/Cas9 Genome Engineering - Turan, S.; Kavyanifar, Atria; Wend, H.; Pozner, Tatyana; Loskam, S.; Kaindl, J.; Lanfer, Jonas; Rizo, Tania; Riedlberger, J. (International Conference on CRISPR Technologies 2019, 2019)
CRIS-Team Scopus Importer:2024-12-16

SoxC transcription factors: multifunctional regulators of neurodevelopment - Kavyanifar, Atria; Turan, Sören; Lie, Dieter Chichung (Cell and Tissue Research, 2018)
During development, generation of neurons is coordinated by the sequential activation of gene expression programs by stage- and subtype-specific transcription factor networks. The SoxC group transcription factors, Sox4 and Sox11, have recently emerged as critical components of this network. Initially identified as survival and differentiation factors for neural precursors, SoxC factors have now been linked to a broader array of developmental processes including neuronal subtype specification, migration, dendritogenesis and establishment of neuronal projections, and are now being employed in experimental strategies for neuronal replacement and axonal regeneration in the diseased central nervous system. This review summarizes the current knowledge regarding SoxC factor function in CNS development and disease and their promise for regeneration.
EVALuna2:34133